A technology-enhanced multiliteracies learning design for geography education - Lori Lockyer,; Barry Harper, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Educators are being challenged to prepare students to effectively participate in our increasingly globalised society. Contemporary views of pedagogy suggest supporting learners by providing scaffolds for their engagement in real world tasks - tasks that provide opportunities to both explore and apply their learning through multi-modal expressions 'within their diverse contexts. This article describes a project that draws upon the emerging views of multiliteracies in the design of a K-12 education excursion program. The multiliteracies learning design developed for the program is applied to specific discipline-focused learning objectives and implemented within a technology-enhanced environment, which provides learners with access to the multimodal texts and tools. A geography based curriculum application is specifically detailed in this article.